Dual Practice by Health Workers: Theory and Evidence from Indonesia - Paula Gonzalez; Gabriel V. Montes-Rojas; Sarmistha Pal (Institute of Labor Economics (IZA), 2017)
Using a simple theoretical model we conjecture that dual practice may increase the number of patients seen but reduce hours spent at public facilities, if public physicians lack motivation and/or if their opportunity costs are very large. Using data from Indonesia, we then test these theoretical conjectures. Our identification strategy relies on a 1997 legislation necessitating health professionals to apply for license for private practice only after three years of graduation. Results using a difference-in-difference regression discontinuity design provides support to our conjectures, identifying the role of weak work discipline, lack of motivation and opportunity costs of public service provision.
Keywords: I10; I18; J2; J44; J45; O1; 330; dual practice of health professionals; Ministry of Health Regulation; weak monitoring; motivation; opportunity costs of public service; Indonesia